Controlled disassembly of a DNA tetrahedron using strand displacement. Issue 3 (2nd January 2019) - Chandrasekaran, Arun Richard; Halvorsen, Ken
Abstract : A DNA tetrahedron is disassembled by nucleic acid triggers via strand displacement, showing promise in the creation of "sense-and-act" nanomachines. Abstract : In this study, we assembled a DNA tetrahedron containing single stranded extensions in the middle of the struts. Using these extensions as toeholds, the tetrahedron can be disassembled by nucleic acid triggers via strand displacement. The release mechanism is sequence specific, is functional in biological fluids such as serum and urine, and the kinetics of the disassembly process can be controlled by different molar ratios of the release strand. Such DNA nanostructures that respond to external stimuli have potential use in biosensing and drug delivery, and we demonstrate a proof-of-concept of this approach for microRNA detection.